2019
DOI: 10.1515/aut-2018-0031
|View full text |Cite
|
Sign up to set email alerts
|

Wicking Behaviors of Ring and Compact-Siro Ring Spun Yarns with Different Twists

Abstract: In this study, the wicking properties of ring and compact-siro ring spun staple yarns were compared. The twist level, which is related to the structure of the staple yarns, was found to significantly influence the wicking property of the two kinds of yarn. Polyester staple fibers with 1.33 dtex × 38 mm were selected as the staple fiber material, and the effect of the twist level on the wicking property was investigated using the capillary rise method. The results show that with a decreasing twist coefficient, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Specifically, at the yarn scale, the key influential factors include spinning system, fiber type, yarn count, structural geometry, applied twist, tensile strain, etc. In recent decades, for example, Lu et al 17 compared the yarn wicking behavior from spinning system and twist perspective, and pointed out that the twist level was found to influence the wickability of traditional ring and compact-siro ring spun staple yarns. The wickability of cotton/acrylic rotor blend yarns increased with an increase in acrylic content inside a rotor yarn and with the use of coarse yarns, reported by Öztürk et al 18 The wicking effect of cotton woven fabrics in different directions and wicking effect of its constituent yarns has been investigated by Mallick and De.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, at the yarn scale, the key influential factors include spinning system, fiber type, yarn count, structural geometry, applied twist, tensile strain, etc. In recent decades, for example, Lu et al 17 compared the yarn wicking behavior from spinning system and twist perspective, and pointed out that the twist level was found to influence the wickability of traditional ring and compact-siro ring spun staple yarns. The wickability of cotton/acrylic rotor blend yarns increased with an increase in acrylic content inside a rotor yarn and with the use of coarse yarns, reported by Öztürk et al 18 The wicking effect of cotton woven fabrics in different directions and wicking effect of its constituent yarns has been investigated by Mallick and De.…”
Section: Introductionmentioning
confidence: 99%
“…The structural parameters of knitted fabrics and majority of physical and mechanical properties depend on the technical characteristics of knitting machine and properties of yarns. The yarn diameter, origin of fibres, knitting structure, course and wale density, yarn twist level and linear density are the main factors affecting the porosity of knitted fabrics [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the prepared TH@CS with the reported materials revealed that the transport height of TH@CS far exceeded that of the other materials (Fig. 3g), 24,25,26,27,28,29 illustrating the great superiority of the core-shell structure and the twofold hierarchical structure for self-driven ultra-long distance anti-gravity water transport.…”
mentioning
confidence: 94%